Slave flights and runaway communities in Angola (17th-19th centuries) - Ferreira, Roquinaldo (Anos 90, 2014)
This article explores slave resistance in Angola by focusing on slave flights and the formation of runaway communities during the era of the transatlantic slave trade from the seventeenth to the nineteenth centuries. It argues that slave flights and runaways communities were integral to societies under Portuguese influence in coastal and internal Angola. It demonstrates that flights occurred due to a wide variety of reasons, including opposition to shipment to Brazil, mistreatments by slave owners, and the influence of African social institutions and customs. Runaways’ fate depended on the willingness of African rulers to taken them as fugitives, and many became part of gangs that disrupted the trade between coastal Angola and slave markets in the interior. The article argues that slave flights and runaway communities became more numerous in the nineteenth century, as the transatlantic slave trade declined and commercial agriculture was established in the Luanda hinterland.